PENGARUH GENDER TERHADAP HASIL PEMBELAJARAN PENCAK SILAT PADA SISWA DI SMP IT NURUL AMANAH TASIKMALAYA - Ai Nurjanah, - (2019)
The research aims to determine gender influence on the results of the learning of Pencak Silat in SMP IT Nurul Amanah Tasikmalaya. The method that used is the experimental research method, design this research using Control Group Post Test Only Design. The population of this research is a class of students VII, VIII, IX of the Islamic Junior High School, Nurul Amanah Tasikmalaya, with Eudora in the middle of 26 students from the Islamic Junior high School, Nurul Amanah Tasikmalaya. Sampling techniques using the Random Sempling technique are divided into two groups of 16 female students as experimental groups and male students as control groups. Data is processed using the Microsoft Office Excel 2010 using the T test. The result of the calculation obtained the calculated T value of 1.9 with a table T value of 1.711 in terms of significance of 0.05, so that the count is within the area Rejection H0 t count ≥ of T table (1.9 ≥ 1.711) then H0 rejected and H1 accepted. So it can be concluded that there is a significant gender influence on the outcome of Pencak Silat learning.